Variations in the distal branches of the superficial fibular sensory nerve. Issue 1 (12th July 2016) - Hemmi, Shoji; Kurokawa, Katsumi; Nagai, Taiji; Kushida, Ryutaro; Okamoto, Toshio; Murakami, Tatsufumi; Sunada, Yoshihide
ABSTRACT: Introduction : We evaluated anatomic variations of distal branches of the superficial fibular sensory nerve electrophysiologically. Methods : Orthodromic nerve conduction studies (NCS) of the first and third branches (M‐I, M‐III) of the medial dorsal cutaneous nerve and the fourth and fifth branches (I‐IV, I‐V) of the intermediate dorsal cutaneous nerve (IDCN) were performed. To find anomalous innervations from the dorsal sural nerve (DSN) in the IDCN territory, NCS of the fourth and fifth branches (S‐IV, S‐V) of the DSN were also performed. Results : All sensory nerve action potentials (SNAPs) of M‐I and M‐III could be obtained bilaterally from 31 healthy Japanese volunteers. SNAPs of I‐IV and I‐V were recordable in 85.5% and 43.5% of feet, respectively. Anomalous innervations from the DSN were confirmed in 71.0% of S‐IV and 93.5% of S‐V. Conclusion : These results suggest that anatomical variations in the IDCN territory are very frequent in Japanese subjects. Muscle Nerve 55 : 74–76, 2017